UDC Online: A Study - Gedam, Pranali B. (Journal of Information and Knowledge, 2015)
In this paper an attempt has been made to highlight the online services provided by UDC Online database. In the modern techno-savvy era, the traditional library classification scheme 'Universal Decimal Classification' has radically changed its structure and published on Web in 2001 entitled' UDC Online'. It has created new opportunities to classifier for searching the term and class numbers, browsing UDC database, number building facility and advance searches. It is a very user friendly scheme in this era of information technology. It is the most updated version on the web, updated annually. It is concluded that it is a prominent and effective knowledge organization tool to classify universe of subjects and provide the fixed place to every things, documents, and electronic items. The databases have been accessed through trial accounts of their official websites.